ANALISIS PELAKSANAAN BIMBINGAN KELOMPOK PADA PESERTA DIDIK KELAS VIII DI SMP 24 PONTIANAK - Fadlun, Egwan; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGroup guidance services are activities that can support learners in an effort to develop their own potential and can utilize their own educational experiences through group dynamics. this study aims to analyze the implementation of group guidance by teachers counseling guidance on students VIII grade SMP Negeri 24 Pontianak. The method used is descriptive method and the form of research is survey form. The population in this study as many as 162 students and the sample in this study as many as 63 students. This research uses quantitative research. Data collecting technique used is indirect communication in the form of questionnaire. Data analysis techniques use the percentage formula. Based on the results of the analysis of group guidance by counseling guidance teachers achieve the score in the category of